Detailed evaluation of different 68Ge/68Ga generators: an attempt toward achieving efficient 68Ga radiopharmacy. (2nd February 2016) - Chakravarty, Rubel; Chakraborty, Sudipta; Ram, Ramu; Vatsa, Rakhee; Bhusari, Priya; Shukla, Jaya; Mittal, B. R.; Dash, Ashutosh
Abstract : The present study is aimed at carrying out a comparative performance evaluation of different types of 68 Ge/ 68 Ga generators to identify the best choice for use in 68 Ga‐radiopharmacy. Over the 1 year period of evaluation, the elution yields from the CeO2 ‐based and SiO2 ‐based 68 Ge/ 68 Ga generators remained almost consistent, in contrast to the sharp decrease observed in the elution yields from TiO2 and SnO2 ‐based generators. The level of 68 Ge impurity in 68 Ga eluates from the CeO2 and SiO2 ‐based 68 Ge/ 68 Ga generator was always <10 −3 %, while this level increased from 10 −3 % to 10 −1 % in case of TiO2 and SnO2 ‐based generators. The level of chemical impurities in 68 Ga eluates from CeO2 and SiO2 ‐based 68 Ge/ 68 Ga generators was negligibly low (<0.1 ppm) in contrast to the significantly higher level (1–20 ppm) of such impurities in eluates from other two generators. As demonstrated by radiolabeling studies carried out using DOTA‐coupled dimeric cyclic RGD peptide derivative (DOTA‐RGD2 ), CeO2 ‐PAN and SiO2 ‐based generators are directly amenable for radiopharmaceutical preparation, whereas the other generators can be only used after post‐elution purification of 68 Ga eluates. Clinically relevant dose of 68 Ga‐DOTA‐RGD2 was prepared in a hospital radiopharmacy for non‐invasive visualization of tumors in breast cancer patients using positron emission tomography. Abstract : Gallium‐68 availed from SiO2 and CeO2 ‐PAN‐based 68 Ge/ 68 Ga generators can directly be used for preparation of clinically relevant doses of 68 Ga‐DOTA‐RGD2, while 68 Ga availed from TiO2 and SnO2 ‐based 68 Ge/ 68 Ga generators needs to be purified prior to radiolabeling procedure.